Effects of chronic liver disease on the outcomes of simultaneous resection of colorectal cancer with synchronous liver metastases: a propensity score matching study - Jiang, Zheng-Jie; Peng, Xu-Dong; Wei, Zheng-Qiang; Tang, Gang (Frontiers in Surgery, 2023)
Given the rising prevalence of chronic liver disease (CLD), it is increasingly important to understand its impact on surgical outcomes. Our aim was to evaluate the impact of CLD on short-term outcomes in patients with colorectal cancer and synchronous liver metastases undergoing simultaneous surgery. We retrospectively reviewed patients with colorectal cancer and liver metastases who underwent simultaneous resection between January 2013 and June 2022. Patients were divided into the CLD and non-CLD groups. Data regarding short-term surgical outcomes were compared between the two groups. A total of 187 patients were included. After propensity score matching, there were 42 patients in each group, and the basic characteristics of the two groups were similar. Patients with CLD had a significantly greater incidence of postoperative complications (47.6% vs. 26.2%; P = 0.042). The operation times of the CLD and non-CLD groups were similar (297 vs. 307.5 min, P = 0.537), and the blood loss was comparable between the two groups (250 vs. 155 mL, P = 0.066). No significant differences were observed between the two groups in pneumonia (P > 0.999), urinary infection rate (P > 0.999), ileus rate (P = 0.474), wound infection rates (P > 0.999), abdominal infection rate (P = 0.533), anastomotic leakage rate (P > 0.999), digestive hemorrhage rate (P > 0.999), bile leakage rate (P > 0.999), hepatic hemorrhage rate (P > 0.999), reoperation rate (P > 0.999), intensive care rate (P > 0.999), or severe liver failure (P > 0.999). There were no deaths in the two groups. CLD significantly prolonged the length of hospital stay (P = 0.011). CLD is an important factor affecting postoperative complications in patients with colorectal cancer liver metastases undergoing simultaneous surgery. Considering the large number of patients with CLD in China, more attention and medical care should be provided to patients with CLD who require simultaneous resection of colorectal cancer with synchronous liver metastases.